The Role of School Policies, Teacher Practices, and Peer Interactions in Creating a Safe and Inclusive Learning Environment - Amrisal, Amrisal; Hamdana, Dian (Educia Journal, 2024)
The purpose of this qualitative study is to determine how schools support safe and productive learning environment and experiences of students, teachers, and school administrators about the actual process. The research employs both semi-structured interviews with students, focus group discussion, and document analysis to establish how school policies; teacher practices; and peer interactions enhance or hinder students’ feeling of safety and inclusion. The narratives indicate that while schools have issued policies against bullying and for inclusiveness, students’ experiences of inclusion depend on the actual practice of enforcing rules against bullying and for acceptance, as well as the culture of acceptance encouraged at the school by the teachers as well as the school officials. The staff cultural competence as well as the staff development is important in handling students’ diversity; while students peer relations are important as far as students’ inclusion is concerned. The findings underline the consistence of the formal procedures with the actual teacher’s practices and supportive peer relations as key factors contributing to a successful, inclusive school. The outcomes also stress the relevance for schools to move from policies’ production as for addressing the problems of supporting the valued social contacts’ availability to students at any level of the school community.